RETRACTED ARTICLE: A naturally occurring Al-Cu-Fe-Si quasicrystal in a micrometeorite from southern Italy - Giovanna Agrosì; Paola Manzari; Daniela Mele; Gioacchino Tempesta; Floriana Rizzo; Tiziano Catelani; Luca Bindi (Communications Earth & Environment)
Abstract Quasicrystals, solids with rotational symmetries forbidden for crystals, are usually synthesized in the laboratory by mixing specific ratios of selected elemental components in the liquid and quenching under strictly controlled protocols. Nevertheless, the discovery of Al-Cu-Fe natural quasicrystals in the Khatyrka meteorite showed that these exotic phases could also form in high-velocity impact-induced shock events introducing an endeavour to search them in cosmic material. Here we report the discovery of an extraterrestrial icosahedral quasicrystal with an unusual composition Al51.7(6)Cu30.8(9)Fe10.3(4)Si7.2(9), ideally Al52Cu31Fe10Si7, found in a scoriaceous micrometeorite, named FB-A1, recovered at the top of Mt. Gariglione (Italy). The chemistry of the icosahedral phase was characterized by electron microprobe, and the rotational symmetry was confirmed by means of electron backscatter diffraction. The FB-A1 micrometeorite represents the third independent discovery of naturally occurring intermetallic Al-Cu-Fe-(Si) alloys in extraterrestrial bodies and the second case of extraterrestrial material containing a natural quasicrystal, after Khatyrka meteorite.